Involvement of the ANGPTs/Tie-2 system in ovarian hyperstimulation syndrome (OHSS) - Scotti, Leopoldina (2013)
Ovarian hyperstimulation syndrome (OHSS) is a disorder associated with ovarian stimulation. OHSS features are ovarian enlargement with fluid shifting to the third space. Disturbances in the vasculature are considered the main changes that lead to OHSS. Our aim was to analyze the levels of angiopoietins 1 and 2 (ANGPT1 and 2) and their soluble and membrane receptors (s/mTie-2) in follicular fluid (FF) and in granulosa-lutein cells culture (GLCs) from women at risk of developing OHSS. We also evaluated the effect of ANGPT1 on endothelial cell migration. In ovaries from an OHSS rat model, we analyzed the protein concentration of ANGPTs, their mTie-2 receptor, and platelet-derived growth factor PDGF-B, -D and PDGFR-β. ANGPT1 levels were increased in both FF and GLCs from women at risk of OHSS. Incubation of these FF with an ANGPT1 neutralizing antibody decreased endothelial cell migration. In the ovaries of OHSS rat model, mTie-2 protein levels increased and PDGF-B and -D decreased. In summary, these results suggest that ANGPT1 could be another mediator in the development of OHSS.